Nanorough gold for enhanced Raman scattering - Kim, Jeonghwan (American Vacuum Society, 2013)
Conventional Raman scattering is a workhorse technique for detecting and identifying complex molecular samples. In surface enhanced Raman scattering, a nanorough metallic surface close to the sample enhances the Raman signal enormously. In this work, the surface is on a clear epoxy substrate. The epoxy is cast on a silicon wafer, using 20 nm of gold as a mold release. This single step process already produces useful enhanced Raman signals. However, the Raman signal is further enhanced by (1) depositing additional gold on the epoxy substrate and (2) by using a combination of wet and dry etches to roughen the silicon substrate before casting the epoxy. The advantage of a clear substrate is that the Raman signal may be obtained by passing light through the substrate, with opaque samples simply placed against the surface. Results were obtained with solutions of Rhodamine 6G in deionized water over a range of concentrations from 1 nM to 1 mM. In all cases, the signal to noise ratio was greater than 10:1.